ANALISIS PENGARUH KUALITAS PRODUK, CITRA MEREK DAN KEPUASAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi pada Mahasiswa Fakultas Ekonomika dan Bisnis Unisbank Semarang Pengguna Handphone Samsung) (Students' Journal of Economic and Management, 2015)
The purpose of this study was to analyze the effect of product quality and brand image on customer satisfaction and customer loyalty Samsung mobile phone. The population in this study were students of the Faculty of Economics and Business, University of Stikubank Semarang who use mobile phones Samsung. The samples in this study using purposive sampling, the sampling technique with a specific purpose. The analysis tool used is multiple linear regression analysis. The results of the analysis can be concluded that: product quality and brand image positive effect on customer satisfaction. Product quality, brand image and customer satisfaction has positive influence on customer loyalty Keywords: product quality, brand image, customer satisfaction and customer loyalty